2015
DOI: 10.1007/s10014-015-0238-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid immunocytochemistry based on alternating current electric field using squash smear preparation of central nervous system tumors

Abstract: The role of intraoperative pathological diagnosis for central nervous system (CNS) tumors is crucial for neurosurgery when determining the surgical procedure. Especially, treatment of Carmustine (BCNU) wafers requires a conclusive diagnosis of high grade glioma (HGG) proven by intraoperative diagnosis. Recently, we demonstrated the usefulness of rapid immunohistochemistry (R-IHC) that facilitates antigen-antibody reaction under alternative current (AC) electric field in the intraoperative diagnosis of CNS t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Furthermore, rapid immunohistochemical methods based on alternating current electric fields are available to facilitate the interaction between antigen and antibody. These methods make it possible to determine the MIB-1 indices and the tumour proliferation activity intraoperatively [29,41]. Therefore, new treatment modalities that can downregulate inflammatory processes and enable the construction of highly personalised therapies, which can be used immediately after VS surgery in high-risk patients with worse postoperative facial nerve outcomes, are needed.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Furthermore, rapid immunohistochemical methods based on alternating current electric fields are available to facilitate the interaction between antigen and antibody. These methods make it possible to determine the MIB-1 indices and the tumour proliferation activity intraoperatively [29,41]. Therefore, new treatment modalities that can downregulate inflammatory processes and enable the construction of highly personalised therapies, which can be used immediately after VS surgery in high-risk patients with worse postoperative facial nerve outcomes, are needed.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…However, there are some operational problems regarding the utilization of MIB‐1 LI. The surgical strategy cannot be modified during surgery based on the MIB‐1 LI result because intraoperative rapid immunohistochemistry is not usually available during surgery . Quantification of the MIB‐1 LI is not impervious to interobserver biases .…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have indicated that the frozen sectioning and squash smears require a sample with a minor axis of at least 1 to 2 mm . Shah et al and Rao et al reported that cytodiagnosis using squash smears was impossible in 14.8% and 6.7% of cases, respectively, although their data may have been based on insufficient amounts of tumor tissue in some cases.…”
Section: Discussionmentioning
confidence: 99%